The phantom of the opera - Schumacher, Joel; Warner Bros. Pictures (United States Warner Home Video, 2004)
A mysterious and disfigured musical genius haunts the Paris Opera House and becomes obsessed with a young soprano, guiding her talent while pursuing a tragic romance that unfolds amid jealousy and intrigue.
Based on the stage musical by Andrew Lloyd Webber and the novel by Gaston Leroux.
Rated PG-13.
Keywords: Opera; Musicals